THE INFLUENCE OF HUMAN RELATIONS AND WORKPLACE PEACE ON EMPLOYEE PERFORMANCE AT THE COOPERATIVES, SME, MANPOWER AND TRANSMIGRATION SERVICE OF SIDENRENG RAPPANG REGENCY - Munawarah, Munawarah; Putri D, A. Kartini Sari; Salam, Mifta Farid (Universitas Ichsan Sidenreng Rappang, 2025)
This study aims to determine the influence of human relations and workplace peace on employee performance at the Cooperatives, SMEs, Manpower and Transmigration Service of Sidenreng Rappang Regency partially and simultaneously. This study uses a quantitative method with a Likert scale using a sample of 51 respondents, the data sources in this study are divided into two, namely primary data obtained directly through observation and secondary data obtained through external references, both articles, journals and others. The sampling technique used is the total sampling technique. The data analysis used is multiple linear regression analysis using Statistical Product and Service Solution (SPSS) version 21. The results of the study indicate that the human relations variable does not have a significant positive effect on employee performance. This is indicated by the calculated t value of -0.698 0.05. So based on these results it can be stated that Human Relations does not affect employee performance. The work peace variable shows that work peace has a positive and significant effect on employee performance. This is indicated by the calculated t value of 4.511 > 1.677 t table value. Also reinforced by the significance value obtained of 0.000 < 0.05. So based on these results it can be stated that work peace can partially provide a positive and significant effect on employee performance. The Human Relations and Work Peace variables simultaneously have a positive and significant effect on employee performance because the significant value of the f-test results (0.000) is less than 0.005.